An Update on the Controversies in Anemia Management in Chronic Kidney Disease: Lessons Learned and Lost. (24th February 2011) - Teehan, Geoffrey; Benz, Robert L.
Abstract : Background . Erythropoietin deficiency and anemia occur in Chronic Kidney Disease (CKD) and may be treated with Erythropoietin Stimulating Agents (ESAs). The optimal hemoglobin, in non-End Stage Renal Disease CKD, is controversial. Methods . We review three recent randomized trials in anemia in CKD: CHOIR, CREATE, and TREAT. Results . CHOIR (N = 1432 ) was terminated early with more frequent death and cardiovascular outcomes in the higher Hb group (HR 1.34: 95% C.I. 1.03–1.74, P = .03 ). CREATE (N = 603 ) showed no difference in primary cardiovascular endpoints. Stroke was more common in the higher Hb group (HR 1.92; 95% C.I. 1.38–2.68;P < .001 ) in TREAT (N = 4038 ). Conclusions . There is no benefit to an Hb outside the 10–12 g/dL range in this population. To avoid transfusions and improve Quality of Life, ESAs should be used cautiously, especially in patients with Diabetes, CKD, risk factors for stroke, and ESA resistance.